ヒガシ ドロンイングモードランド セール・ロンダーネ サンチ チガク チョウサタイ ホウコク 2009–2010(JARE-51) - 土屋, 範芳; ツチヤ, ノリヨシ; 石川, 正弘; イシカワ, マサヒロ; Satish-Kumar, Madhusoodhan; 河上, 哲生; カワカミ, テツオ; 小島, 秀康; コジマ, ヒデヤス; 海田, 博司; カイデン, ヒロシ; 三浦, 英樹; et al. (2012)
P(論文) セール・ロンダーネ山地は,東南極・東ドロンイングモードランドに位置している.第51 次日本南極地域観測隊(JARE-51)夏隊の一部は2009-2010年の夏期に,セール・ロンダーネ山地においてベルギー南極観測隊(BELARE)との国際共同により地質,地形,隕石探査の地学野外調査を実施した.地質隊と地形隊はドロンイングモードランド航空ネットワーク(DROMLAN)によりセール・ロンダーネ山地に赴き,隕石探査隊は日本の新南極観測船「しらせ」の処女航海として南極に到着した.地質隊は山地東部を含むセール・ロンダーネ山地のほぼ全域をカバーし,地形隊は山地の西部および中央部で調査を行った.隕石探査隊は山地東部で調査を行った.野外活動は安全かつ成功裏に終了した.地質隊の一部はDROMLAN により帰国し,他のメンバーはセール・ロンダーネ山地からDROMLAN により昭和基地へ離脱したのち,「しらせ」により帰国した.本稿では設営,気象を含めた野外行動全般について報告する. Earth science-related field activities, involving geology, geomorphology and meteorite searches, were carried out in the Sør Rondane Mountains, Eastern Dronning Maud Land, during the 2009-2010 summer season as a part of the 51st Japanese Antarctic Research Expedition (JARE-51), in collaboration with the Belgian Antarctic Research Expedition (BELARE). Geology and geomorphology parties accessed the Sør Rondane Mountains using the Dronning Maud Land Air Network (DROMLAN), and the meteoritesearch party to Antarctica on the maiden voyage by the new Japanese icebreaker Shirase. The geology party covered the entire area of the Sør Rondane Mountains, although with an emphasis on the eastern part. The geomorphology party carried out fieldwork in western and central parts of the mountains, and the meteorite search party performed a survey in the eastern part. All field activities were succes fully carried out. Some of the geology members returned to Japan by DROMLAN, while others flew to Syowa Station from the Sør Rondane Mountains by DROMLAN, and then returned to Japan on board Shirase. This report provides a summary of the field operations, including logistics and weather records. departmental bulletin paper